Rembrandt is in the wind : learning to love art through the eyes of faith - Ramsey, Russ, 1973- (Grand Rapids Zondervan, 2022)
"Rembrandt Is in the Wind by Russ Ramsey is part art history, part biblical study, part philosophy, and part analysis of the human experience; but it's all story. An invitation to discover some of the world's most celebrated artists and works, it presents the beauty of the gospel in a way that speaks to our most common struggles and longings"--
Includes bibliographical references (pages 235-256).
Keywords: Christianity and art; Christianity and the arts; Aesthetics -- Religious aspects -- Christianity